2010
DOI: 10.1038/cgt.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting protective immune responses against murine myeloma challenge in lymphopenia mice through adoptive transfer of tumor antigen-specific lymphocytes and immunization of tumor vaccine secreting mIL-21

Abstract: Previous studies have indicated that the cytokine interleukin (IL)-21 may induce both innate and adaptive immune responses against tumors. The goal of this study was to evaluate a new adoptive immunotherapy strategy that combined lymphocytes from mice immunized with a murine myeloma vaccine secreting murine IL-21 (mIL-21-Sp2/0) in lymphopenic mice induced by cyclophosphamide. The data indicate that effective antitumor immunity was induced in mice receiving syngeneic murine lymphocytes from the mice immunized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The Kit is suitable for detection of samples including cell culture supernatant and serum, and the sensitivity of Kit is 5.3 pg/mL [23,24]. …”
Section: Methodsmentioning
confidence: 99%
“…The Kit is suitable for detection of samples including cell culture supernatant and serum, and the sensitivity of Kit is 5.3 pg/mL [23,24]. …”
Section: Methodsmentioning
confidence: 99%
“…In particular, the mice that received the B16F10/GPI-IL-21 vaccination combined with the B16F10/shTGF-β1 challenge and the administration of miR200c agomir showed stronger CTL and NK activities and lower CD4 + CD25 + Treg cells than any other mice; these treated mice also showed a reduction in the serum TGF-β1 level and an increase in the IFN-γ level. It has been reported that IFN-γ can react to NK cells and CTL, enhance their cytotoxic activities, and play a key biological role in killing tumor cells or inducing tumor cell apoptosis [ 19 - 21 ]. Malignant melanomas secrete high amounts of TGF-β, and the increased circulating plasma concentration is asso­ciated with the advanced stage of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…A murine IL-21-secreting whole myeloma cell vaccine (mIL-21-Sp2/0) has also been used to prime immune responses against myeloma in vivo. Lymphocytes from mIL-21-Sp2/0-immunized mice infused in mice lymphodepleted by cyclophosphamide treatment induced protective immunity against murine myeloma [ 106 ]. Besides tumor cells, also other cell types transduced with IL-21 gene proved to be effective at inducing antitumor responses.…”
Section: Preclinical Studies Of Il-21 Cancer Immunotherapymentioning
confidence: 99%